FILICIDE IN DEPRESSIVE PSYCHOSIS: CASE REPORT OF AN EMOTIONALLY UNSTABLE WOMAN SLAUGHTERING HER TWO CHILDREN - Zubair, Usama Bin; Taj, Rizwan; Ali, Syed Azhar; Kayani, Asma; Khan, Asima Mehboob (Journal of Ayub Medical College Abbottabad, 2020)
Filicide is the murder of a child by the parent. It is associated with various psychiatric and non-psychiatric conditions. We herein present a case report of a filicide by an emotionally unstable mother suffering from depressive psychosis. A thirty years old woman previously treated for depression with psychotic features, having undergone electro-convulsive therapy and on oral medication three years ago was brought by the police for psychiatric assessment. She had slaughtered her two sons of 4 and 7 years of age three days ago without any guilt or remorse. She had low mood, irritability, crying spells, hopelessness and loss of sleep, appetite and sexual desires for the past six months along with the delusions of poverty and infidelity for the past two months. She was a chain smoker. Multiple deliberate self-harm and suicidal attempts were reported in the past two months. She had disturbed family life and multiple conflicts with the husband. Psychometrics revealed BDI score of 32, BPRS score of 39 and PCL-R score of 28. She was diagnosed as a case of depressive psychosis with emotionally unstable personality traits leading to impaired judgment and poor comprehension of the consequences of her actions. This case report highlights the importance of accurately and timely diagnosing and managing a mental health disorder in order to avoid the harm towards self and others. Keywords: filicide; depressive psychosis; forensic psychiatry